Komposisi gizi tahu kombinasi dari kacang tunggak dan kedelai yang dibuat dengan bahan penggumpal asam cuka dan biang tahu - Wahyu Mushollaeni; Lorine Tantalu; Melkianus Malo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
One of the typical foods consumed daily as a side dish by the community is tofu. Tofu is made with soybean as raw material which is crushed into a pulp and protein coagulated to form the texture of the tofu. Until now, soybeans are the main raw material for making tofu. In fact, according to the analysis, the projection of soybean demand is much higher than the supply of soybeans that can be produced, so that the potential to meet the demand for soybeans will be carried out through imports. Imported soybeans will affect the selling price of tofu because the price of imported soybeans varies depending on the exchange rate and under certain conditions, the price of imported soybeans is cheaper. If this condition continues, the original tofu made from local soybeans will be crushed by the use of imported soybeans, farmers will lose because local soybeans are not selling well, tofu traders suffer a lot, the price of tofu varies, and it is possible to reduce the original taste of local tofu. Therefore, it is necessary to have raw materials that can substitute soybeans in making tofu, including cowpeas. This study aims to determine the combination of cowpea-soybean formulations and coagulation ingredients to produce the best physicochemical quality of tofu. The best treatment is the use of a combination of 90% soybeans with 10% cowpeas and vinegar as a coagulant for protein. The treatment resulted in tofu with levels of protein, fat, fiber, carbohydrates, water, and ash, respectively 12.10%; 2.8%; 0.6%; 9.29%; 71.56%; and 3.64%.